A Clot Model Examination: with Impulsion of Nanoparticles under Influence of Variable Viscosity and Slip Effects. (November 2017) - Ijaz, S.; Shahzadi, Iqra; Nadeem, S.; Saleem, Anber
Abstract: In this speculative analysis, our main focused is to address the neurotic condition that occurs due to accumulation of blood components on the wall of the artery that results in blood coagulation. Specifically, to perceive this phenomena clot model is considered. To discuss this analysis mathematical model is formed in the presence of the effective thermal conductivity and variable viscosity of base fluid. Appropriate slip conditions are employed to obtain the close form solutions of temperature and velocity profile. The graphical illustrations have been presented for the assessment of pressure rise, pressure gradient and velocity profile. The effects of several parameters on the flow quantities for theoretical observation are investigated. At the end, the results confirmed that the impulsion of copper and silver nanoparticles as drug agent enlarges the amplitude of the velocity and hence nanoparticles play an important role in engineering and biomedical applications such as drug delivery system.